Peningkatan Skala Produksi Mikroenkapsulat Minyak Sawit Merah dengan Pengering Semprot - Dede R. Adawiyah; Leonardus B. Raditya Prabowo; Purwiyatno Hariyadi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2019)
Red palm oil (RPO) contains high carotene which can be used as coloring agent and source of provitamin A. Drying technology by means of spray dryer is used in order to concomitantly reduce moisture content of RPO microencapsulates and maintain its carotene content. The objective of this research was to study the scale-up process of the RPO microencapsulate production from laboratory scale (8.3 mL/min) to pilot plant scale (300 mL/min). At laboratory scale, using Buchi 190 spray dryer, the optimum formulation of (Maltodextrin:Gum Arabic) : RPO was (35:15) : 40 or 0.8 parts of RPO compared to one part of microencapsulate coating. At pilot-scale (i.e., 300 mL/minute), the optimum formulation from lab-scale could not be considered as the optimum one based on carotene content as main parameter. At constant parameter inlet temperature of 215oC, outlet temperature of 110oC, pump pressure of 4.5 bar, cyclon speed of 2500 m3/hour, and flow rate of 300 mL/minute, the best microencapsulates could be produced at ratios of coating agent and RPO ranging from 1:0.3-1:0.6. At pilot scale, flow rate and droplet size were the most important factors in order to produce the dry microencapsulates.